Design Of A Doherty Power Amplifier For GSM Systems - Saad Wasmi Osman (Tikrit Journal of Engineering Sciences, 2013)
This paper presents the design and analysis of Doherty power amplifier. The Doherty amplifier is used in  a base station for mobile system because of its high efficiency. The class AB power amplifier used in the configuration of the main and auxiliary amplifier. The result obtained shows that the Doherty power amplifier can be used on a wide band spectrum, the amplifier works at 900MHz and has very good power added efficiency (PAE) and gain. The amplifier can also work at 1800MHz at input power greater than 20dBm.